Structural and Clinical Correlates of a Periventricular Gradient of Neuroinflammation in Multiple Sclerosis. (6th April 2021) - Poirion, Emilie; Tonietto, Matteo; Lejeune, François-Xavier; Ricigliano, Vito A.G.; Boudot de la Motte, Marine; Benoit, Charline; Bera, Géraldine; Kuhnast, Bertrand; Bottlaender, Michel; Bodini, Benedetta; Stankoff, Bruno
Abstract : Objectives: To explore in vivo innate immune cell activation as a function of the distance from ventricular CSF in patients with multiple sclerosis (MS) using [ 18 F]-DPA714 PET and to investigate its relationship with periventricular microstructural damage, evaluated by magnetization transfer ratio (MTR), and with trajectories of disability worsening. Methods: Thirty-seven patients with MS and 19 healthy controls underwent MRI and [ 18 F]-DPA714 TSPO dynamic PET, from which individual maps of voxels characterized by innate immune cell activation (DPA+) were generated. White matter (WM) was divided in 3-mm-thick concentric rings radiating from the ventricular surface toward the cortex, and the percentage of DPA+ voxels and mean MTR were extracted from each ring. Two-year trajectories of disability worsening were collected to identify patients with and without recent disability worsening. Results: The percentage of DPA+ voxels was higher in patients compared to controls in the periventricular WM ( p = 6.10e-6) and declined with increasing distance from ventricular surface, with a steeper gradient in patients compared to controls ( p = 0.001). This gradient was found in both periventricular lesions and normal-appearing WM. In the total WM, it correlated with a gradient of microstructural tissue damage measured by MTR ( r s = −0.65, p = 1.0e-3). Compared to clinically stable patients, patients with disability worsening were characterized by a higher percentage of DPA+ voxels in the periventricular normal-appearing WM ( p = 0.025). Conclusions: Our results demonstrate that in MS the innate immune cell activation predominates in periventricular regions and is associated with microstructural damage and disability worsening. This could result from the diffusion of proinflammatory CSF-derived factors into surrounding tissues.